Dropship Strategy In The Leather Industry - Ria Arifianti; Arbi Abdul Kahfi; Tribowo Rachmat Fauzan (SEAN Institute, 2024)
Dropshippers have a role to promote and sell company products. This research aims to reveal the dropshipping business process on the Shopee application and the use of social media Instagram and TikTok by a business actor named Anne Leather. This type of research is descriptive using qualitative methods to present all business processes from sales and ordering to delivery of goods to consumers. Data was collected through observation, interviews and documentation. Data analysis techniques through interactive model analysis form data reduction, data presentation, and drawing up conclusions. This research shows that in this Dropship System, there are three related actors: buyers, suppliers and dropshippers. The dropshipping business process for Anne Leather's business begins with recording orders and communicating via the Shopee application and social media TikTok and Instagram. Dropshippers don't need to buy goods, don't need to carry out stock, don't need to pack and send goods, the supplier carries out all these processes. Consumers can make transactions via the Shopee application with drop shippers. Delivery of goods will occur if there is a transaction in which the consumer transfers the money to the designated bank, and the wholesaler will send the goods to the consumer. The supplier provides goods that have been agreed with the drop shipper and sends them to consumers. Thus, this dropship strategy is needed to increase sales for leather entrepreneurs and profits for intermediaries (dropshippers). Apart from that, it is easy to carry out sales transactions for consumers.